Do people living with HIV experience greater age advancement than their HIV-negative counterparts?. (1st February 2019) - De Francesco, Davide; Wit, Ferdinand W.; Bürkle, Alexander; Oehlke, Sebastian; Kootstra, Neeltje A.; Winston, Alan; Franceschi, Claudio; Garagnani, Paolo; Pirazzini, Chiara; Libert, Claude; Grune, Tilman; Weber, Daniela; et al.
Abstract : Objectives: Despite successful antiretroviral therapy, people living with HIV (PLWH) may show signs of premature/accentuated aging. We compared established biomarkers of aging in PLWH, appropriately chosen HIV-negative individuals, and blood donors, and explored factors associated with biological age advancement. Design: Cross-sectional analysis of 134 PLWH on suppressive antiretroviral therapy, 79 lifestyle-comparable HIV-negative controls aged 45 years or older from the Co-morBidity in Relation to AIDS (COBRA) cohort, and 35 age-matched blood donors. Methods: Biological age was estimated using a validated algorithm based on 10 biomarkers. Associations between 'age advancement' (biological minus chronological age) and HIV status/parameters, lifestyle, cytomegalovirus (CMV), hepatitis B (HBV) and hepatitis C virus (HCV) infections were investigated using linear regression. Results: The average (95% CI) age advancement was greater in both HIV-positive [13.2 (11.6–14.9) years] and HIV-negative [5.5 (3.8–7.2) years] COBRA participants compared with blood donors [−7.0 (−4.1 to −9.9) years, both P 's < 0.001)], but also in HIV-positive compared with HIV-negative participants ( P  < 0.001). Chronic HBV, higher anti-CMV IgG titer and CD8 + T-cell count were each associated with increased age advancement, independently of HIV-status/group. Among HIV-positive participants, age advancement was increased by 3.5 (0.1–6.8) years among those with nadir CD4 + T-cell count less than 200 cells/μl and by 0.1 (0.06–0.2) years for each additional month of exposure to saquinavir. Conclusion: Both treated PLWH and lifestyle-comparable HIV-negative individuals show signs of age advancement compared with blood donors, to which persistent CMV, HBV co-infection and CD8 + T-cell activation may have contributed. Age advancement remained greatest in PLWH and was related to prior immunodeficiency and cumulative saquinavir exposure. Abstract : Supplemental Digital Content is available in the text